Does Extremely Low Birth Weight Predispose to Low-Renin Hypertension?. Issue 3 (March 2017) - Raaijmakers, Anke; Zhang, Zhen-Yu; Claessens, Jolien; Cauwenberghs, Nicholas; van Tienoven, Theun Pieter; Wei, Fang-Fei; Jacobs, Lotte; Levtchenko, Elena; Pauwels, Steven; Kuznetsova, Tatiana; Allegaert, Karel; Staessen, Jan A.
Abstract : Low birth weight and prematurity are risk factors for hypertension in adulthood. Few studies in preterm or full-term born children reported on plasma renin activity (PRA). We tested the hypothesis that renin might modulate the incidence of hypertension associated with prematurity. We enrolled 93 prematurely born children with birth weight <1000 g and 87 healthy controls born at term, who were all examined at ≈11 years. Renal length and glomerular filtration rate derived from serum cystatin C were 0.28 cm (95% confidence interval, 0.09–0.47) and 11.5 mL/min per 1.73 m 2 (6.4–16.6) lower in cases, whereas their systolic/diastolic blood pressure (BP) was 7.5 mm Hg (4.8–10.3)/4.0 mm Hg (2.1–5.8) higher ( P <0.001 for all). The odds of having systolic prehypertension or systolic hypertension associated with extreme low birth weight were 6.43 (2.52–16.4; P <0.001) and 10.9 (2.46–48.4; P =0.002). Twenty-four hours of urinary sodium excretion was similar in cases and controls (102.1 versus 106.8 mmol; P =0.47). Sodium load per nephron was estimated as sodium excretion divided by kidney length (mmol/cm). PRA was 0.54 ng/mL per hour (0.23–0.85; P =0.001) lower in cases. PRA, systolic BP, and sodium load were available in 43 cases and 56 controls. PRA decreased with systolic BP (slope −0.022 ng/mL per hour/ − mm Hg ; P =0.048), but was unrelated to sodium load (slope +0.13 mmol/cm − mm Hg ; P =0.54). The slope of PRA on systolic BP was similar ( P =0.17) in cases and controls. In conclusion, extremely low birth weight predisposes young adolescents to low-renin hypertension, but does not affect the inverse association between PRA and BP. Clinical Trial Registration—: URL:https://www.clinicaltrials.gov . Unique identifier: NCT02147457.